1996
DOI: 10.1063/1.531633
|View full text |Cite
|
Sign up to set email alerts
|

Gamow states as continuous linear functionals over analytical test functions

Abstract: The space of analytical test functions , rapidly decreasing on the real axis ͑i.e., Schwartz test functions of the type S on the real axis͒, is used to construct the rigged Hilbert space ͑RHS͒ ͑,H,Ј͒. Gamow states ͑GS͒ can be defined in RHS starting from Dirac's formula. It is shown that the expectation value of a selfadjoint operator acting on a GS is real. We have computed exactly the probability of finding a system in a GS and found that it is finite. The validity of recently proposed approximations to calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 24 publications
(14 reference statements)
1
41
0
Order By: Relevance
“…If E is a negative real number (or complex), then there are no coefficients of χ(r; E) in (9) for which the boundary conditions (12) can be satisfied unless they are trivially zero. To be more precise, if E is a complex or a negative real number, the corresponding eigensolution χ(r; E) of Eq.…”
Section: 16mentioning
confidence: 99%
“…If E is a negative real number (or complex), then there are no coefficients of χ(r; E) in (9) for which the boundary conditions (12) can be satisfied unless they are trivially zero. To be more precise, if E is a complex or a negative real number, the corresponding eigensolution χ(r; E) of Eq.…”
Section: 16mentioning
confidence: 99%
“…By recalling Eqs. (20) and (21), we apply the residue theorem to initial data in Φ ± [18] and get two different expansions in GV:…”
Section: Quantization Of a Damped Motionmentioning
confidence: 99%
“…Despite these mathematical properties have been studied by several authors [18][19][20][21][22][23][24][25], a direct physical evidence of their implications is lacking, even in the simplest case of RHO. In this manuscript, we review the basics of TA-QM and of the GV approach to the RHO.…”
Section: Introductionmentioning
confidence: 99%
“…In three previous papers [1,2,3] we have shown that Gamow-states [4] can be interpreted as Sebastiao e Silva's Ultradistributions [5,6,7], whose proper treatment appeals to Rigged Hilbert Space [8,9,10].…”
Section: Introductionmentioning
confidence: 99%